2024
DOI: 10.32604/or.2023.042228
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on nano-phyto-formulations based therapeutic intervention for cancer treatment

ABHISHEK WAHI,
MAMTA BISHNOI,
NEHA RAINA
et al.

Abstract: Cancer is a leading cause of death globally, with limited treatment options and several limitations. Chemotherapeutic agents often result in toxicity which long-term conventional treatment. Phytochemicals are natural constituents that are more effective in treating various diseases with less toxicity than the chemotherapeutic agents providing alternative therapeutic approaches to minimize the resistance. These phytoconstituents act in several ways and deliver optimum effectiveness against cancer. Nevertheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 117 publications
(136 reference statements)
0
0
0
Order By: Relevance
“…Numerous studies in the literature have shown that nanoformulations exhibit higher anti-tumor toxicity than conventional therapies at equivalent concentrations, as well as a lower IC 50 . [38][39][40][41] The advantages of these nanoformulations are illustrated in Figure 1.…”
Section: Application Of Nanoparticles In Cancer Therapymentioning
confidence: 99%
“…Numerous studies in the literature have shown that nanoformulations exhibit higher anti-tumor toxicity than conventional therapies at equivalent concentrations, as well as a lower IC 50 . [38][39][40][41] The advantages of these nanoformulations are illustrated in Figure 1.…”
Section: Application Of Nanoparticles In Cancer Therapymentioning
confidence: 99%